CREATION OF A DIGITAL MODULE AS LEARNING MEDIA FOR DEAF STUDENT'S - Hermanto, Moch. Irwan; Astuti, Eka Yuli; Septiana, Fajar Indra; Suwandari, Lilis; Mastiani, Emay; Effendi, Zulfa Rahmah; Adhimah, Sadiyatu Nuh (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2023)
Deaf people have learning characteristics that rely more on visual aspects. This research aimed to produce learning media in the form of digital module that could accommodate the needs and learning characteristics of deaf students in the course of thesis guidance theory course. This research belonged to the type of development by applying the ADDIE procedure. The results showed that the digital module scored 85.28% in the aspect of the validity test by learning media experts and deafness experts. While in the test practicality by students, the digital module received a score of 85.63%. These two scores indicated that both digital modules were at a very high level of validity and practicality. Subsequently, they were worthy of being a learning media option that could be used for deaf students.